The Relationship between the Use of Website-Based Child Learning Outcome Reports and Academic Supervision in Early Childhood Education (PAUD) - Asep Kurnia Jayadinata; Hafiziani Eka Putri; Dhea Ardiyanti; Khairunisa Al-Izzati Kusuma; Lutfiah Nur Azizah; Ridha Aulia Safitri; Ulfa Sa’adah Hidayat (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
One form of evidence of technological advancement in the field of education is marked by the emergence of the implementation of website-based learning outcome reports, which facilitate educators and educational staff in accessing and managing children’s learning outcomes more flexibly. However, it has not been significantly evident whether this implementation is associated with early childhood education (PAUD) management, particularly academic supervision. This article was prepared and initiated with the aim of determining the relationship between website-based learning outcome reports and academic supervision in PAUD. The study was designed using a non-parametric statistical design as a quantitative research method. The research sample was taken from educators and educational staff at one PAUD institution. The data collection technique used was a questionnaire employing a 1–4 Likert scale model. The bivariate data analysis applied was the Kendall’s Tau correlation test using SPSS 26. The results obtained from a total of 8 respondents with 18 questionnaire items indicate that the relationship between learning outcome reports and academic supervision is at a percentage of 16.6% based on the Kendall’s Tau test. The calculated correlation coefficient (r) of 0.408 indicates a moderate level of correlation. The significance test shows a p-value of 0.178 > 0.05 (α = 0.05), thus Ha is accepted and Ho is rejected. Therefore, it can be concluded that there is a positive relationship with a moderate level between website-based learning outcome reports and academic supervision in early childhood education (PAUD).